Teachers’ Perception of Homework Effectiveness in Primary Grades (Journal of Education and Educational Development, 2023)
Homework has been a part of a traditional lesson plan for a long time. It has been a means to reinforce knowledge transferred in the classroom. This study, using the quantitative method, analyzed school teachers’ perceptions of homework in primary grades. A purposive sampling technique was used to select 88 primary school teachers, teaching different subjects and having different teaching experiences, to participate in the survey. Results derived from data showed that the majority of teachers, teaching different subjects favored giving homework to primary students. Teachers with most teachers in this group had a neutral opinion of homework. Though parents in this study supported homework, they were not in favor of utilizing most of their time in assisting their children to complete their homework. The findings of this study are important to teachers, school administrators, and education policymakers, who need to instill not only the importance of homework but also ensure that homework works as a bridge to foster the parent-child relationship and develop skills to adjust in society. This study recommends that future researchers interview teachers and parents to collect rich data that can be triangulated with the survey to draw more effective conclusions.